2020
DOI: 10.3390/applmech1010003
|View full text |Cite
|
Sign up to set email alerts
|

Spherical Cavity Expansion Approach for the Study of Rigid-Penetrator’s Impact Problems

Abstract: In recent years, Spherical Cavity Expansion (SCE) theory has been extensively utilized to model dynamic deformation processes related to indentation and penetration problems in many fields. In this review, the SCE theory is introduced by explaining the different mathematical features of this theory, its solution, and a potential application to model the penetration of a rigid penetrator into a deformable target. First, a chronologically literature review of the most common models used to study this kind of pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Cavity pressure is given by p c = σ r ( r = a ) , where σ r is the radial stress component, which is related to the oil-based modeling clay material response through the effective stress calculated as σ e = σ θ σ r , 31 where σ θ is the circumferential stress component. Given the fact that oil-based modeling clay is a nearly incompressible material, its response in terms of stresses, density and radial velocity can be determined by the following set of equations: 30,3537…”
Section: Gravitational Drop Test As a Cavity Expansion Mathematical M...mentioning
confidence: 99%
See 2 more Smart Citations
“…Cavity pressure is given by p c = σ r ( r = a ) , where σ r is the radial stress component, which is related to the oil-based modeling clay material response through the effective stress calculated as σ e = σ θ σ r , 31 where σ θ is the circumferential stress component. Given the fact that oil-based modeling clay is a nearly incompressible material, its response in terms of stresses, density and radial velocity can be determined by the following set of equations: 30,3537…”
Section: Gravitational Drop Test As a Cavity Expansion Mathematical M...mentioning
confidence: 99%
“…In the scientific literature, 31,37,39 it have been shown that p c can be expressed as a power-law relation of the non-dimensional cavity expansion velocity:…”
Section: Gravitational Drop Test As a Cavity Expansion Mathematical M...mentioning
confidence: 99%
See 1 more Smart Citation
“…In [20,21], studies on the dynamic deformations produced by spherical projectiles at high speeds are presented. We consider that the level of energies produced during the interaction between the target and the projectile is too high to make comparisons with the present situation, and subsequently these studies are not suitable for determining indentations with much smaller dimensions, as found in the case of pretensioning systems.…”
mentioning
confidence: 99%
“…dρ dt + ρ (v r,r + v z,z ) = − ρur r dρ * dt = dρ dt h (ρ − ρ * )h dρ dtSpherical Cavity Expansion (SCE)[168] ∂σr ∂t + 2 σr−σθ r = −ρ ∂v ∂t + v∂v ∂r Cylindrical Cavity Expansion (CCE) or Disc or Orthogonal layers model [42]F d (t) = F z + A .R t) + B R(t)..R(t)F z = − 1 2 τ 0 (t) ln(ε L ) A = − 1 2 ρ 0 1 − ρL ρ0 ln(ε L ) , B = − 1 2 ρ L ln(ε L )] Modified Archimedes' law [46] F d = k ∅ ρ s g V div (hẑ)dV = k ∅ ρ s g VNon-linear differential area force law (DAFL)[65] …”
mentioning
confidence: 99%